Penerapan Analisis Mengenai Dampak Lingkungan (AMDAL) sebagai Pengelolaan Lingkungan Hidup dan Sungai - Rangkuti, Uday Ihza Mahendra; Fadillah, Muhammad Rizky; Rafif, M. Khaiyir; Hasibuan, Abdurrozzaq (Medan Resource Center, 2023)
This article aims to discuss the application of EIA in environmental and river management. Environmental Impact Analysis (AMDAL) is a study of the major and significant impacts of a planned business and or activity on the environment which is necessary for the decision-making process regarding the implementation of a business and or activity in Indonesia. This AMDAL is made when planning a project that is expected to have an impact on the surrounding environment. This research is a type of qualitative research with a descriptive approach and uses library research methods. The results of the research show that environmental impact analysis can provide benefits for all parties, both for the government, the business world, and the local community.